The construction of 3D hierarchical CdS/NiAl-LDH photocatalyst for efficient hydrogen evolution. (19th January 2023) - Gao, Gaimei; Yang, Guang; Dou, Mingyu; Kang, Shirong; Yin, Xingliang; Yang, Hua; Yang, Wenning; Li, Dacheng; Dou, Jianmin
Abstract: The development of excellent photocatalysts for hydrogen evolution is of great significance to solving the global energy crisis. In this work, a novel 3D hierarchical CdS/NiAl-LDH photocatalyst was fabricated by a facile electrostatic assembly strategy, which was composed of 1D CdS nanorods and 3D flower-like NiAl-LDH microspheres. Under the visible irradiation, the CNA-20 hierarchical photocatalyst presents the optimum hydrogen evolution rate achieved to 3.24 mmol g −1 h −1, which is improved 6.23-fold in comparison with the pure CdS. Through the analysis of energy band structures and first-principles calculation, the type-Ⅱ charge transfer mechanism was proposed. Driven by the built-in electric field, as well as the effect of intimate interface contact of CdS and NiAl-LDH, the photogenerated charge could be achieved rapidly separate and migrate, which effectively promotes the H2 evolution. This well-designed synergistic 1D/3D interface interaction and provides an economic approach to rationally developing metal-free photocatalysts for hydrogen production. Graphical abstract: Image 1 Highlights: A novel 3D hierarchical CdS/NiAl-LDH photocatalyst was fabricated by the electrostatic self-assembly strategy. The CdS/NiAl-LDH photocatalyst displays excellent H2 production activity and stability. DFT calculations helped to explain the charge transfer at the heterojunction interface between CdS and NiAl. A possible charge transfer mechanism during the photocatalytic H2 evolution was proposed.